The United States Steel Corporation and Industrial Stabilization - Berglund, Abraham (Quarterly Journal of Economics, 1924)
The study of the influence of combinations upon industrial stabilization is socially significant, 608. — Growth and general character of the products of the iron and steel industry, 609. — The five-year moving average used as a basis for measuring fluctuations in production, 610. — Comparison of average deviations from our moving average in the cases of pig iron, crude steel, and rolled iron and steel show greater fluctuation in output since the establishment of the Steel Corporation than before it, 612. — Annual fluctuations since 1901 are more abrupt and pronounced in years of depression than in years of expansion, 616. — They average less in the war and post-war years than in the period immediately preceding the war, 616. — Output of rails for the years 1880–1901 and 1902–22 shows less difference in average deviation than steel products generally; but during the period 1902–15, when prices were rigidly fixed, fluctuations were very great, 618. — Average numbers of workers employed each year by the Steel Corporation show less deviation from our moving average than do figures for output, 622. — The larger percentages for variation in production during the period succeeding the establishment of the Steel Corporation are due to large and drastic curtailments in years of depression, 626. — The promptness with which recovery takes place may furnish some support for the contention that in the long run price stabilization makes for industrial stabilization, 630.